ТЕОРИТИЧЕСКИЙ АНАЛИЗ ВЗАИМНОЙ СИСТЕМЫ Mg2+, 2K+,//2C1-, SO42- - H2O В ПРОЦЕССЕ ПОЛУЧЕНИЯ СУЛЬФАТА КАЛИЯ - Абдуллаева Розанна Мирзатуллаевна (Scientific Trends, 2025)
This article examines the peculiarities of the use of color designations in the medical terminology of the Russian and Uzbek languages. Differences in the semantic interpretation of colors, the influence of cultural traditions on their perception and the role of the color palette in diagnostics and medical communication are considered. A comparative analysis of lexemes associated with the main colors (white, red, blue, yellow, black) is given, and differences in their formal and folk use are revealed. Attention is paid to how borrowings from Latin and Greek influenced the terminological system of the Russian language, while in the Uzbek medical vocabulary there is a close connection with national ideas about diseases and their symptoms.
Keywords: Color designations, medical terminology, Russian language, Uzbek language, semantics, symbolism, cultural differences, medical vocabulary.